A treasury of pony stories - Jennings, Linda M.; Lewis, Anthony (Kingfisher London, 1996)
First published in 1996, a collection of sixteen pony stories by such authors as Christine Pullein-Thompson and Adele Geras. Includes folktales from America, France, Scotland and a Greek legend. Illustrated in black and white by Anthony Lewis.